2021
DOI: 10.1073/pnas.2021102118
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and characterization of bromodomain 2–specific inhibitors of BRDT

Abstract: Bromodomain testis (BRDT), a member of the bromodomain and extraterminal (BET) subfamily that includes the cancer targets BRD2, BRD3, and BRD4, is a validated contraceptive target. All BET subfamily members have two tandem bromodomains (BD1 and BD2). Knockout mice lacking BRDT-BD1 or both bromodomains are infertile. Treatment of mice with JQ1, a BET BD1/BD2 nonselective inhibitor with the highest affinity for BRD4, disrupts spermatogenesis and reduces sperm number and motility. To assess the contribution of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…The BD1 and BD2 domains of each family member show a high level of homology (see the Supporting Information, Figure S2); however, there are some key differences in the binding site residues between these domains, which can be exploited to obtain selectivity . Indeed a number of highly selective compounds that bind preferentially to the four BD1 or four BD2 domains of this family have now been reported. It has been shown that the selective inhibition of the BD1 or BD2 domains of the BET proteins results in distinct biological phenotypes; , BD1-selective inhibitors appear to mostly phenocopy pan-BET, especially in oncology, while BD2-selective inhibitors show a more nuanced phenotype appropriate for the treatment of immune-mediated inflammatory diseases …”
Section: Introductionmentioning
confidence: 99%
“…The BD1 and BD2 domains of each family member show a high level of homology (see the Supporting Information, Figure S2); however, there are some key differences in the binding site residues between these domains, which can be exploited to obtain selectivity . Indeed a number of highly selective compounds that bind preferentially to the four BD1 or four BD2 domains of this family have now been reported. It has been shown that the selective inhibition of the BD1 or BD2 domains of the BET proteins results in distinct biological phenotypes; , BD1-selective inhibitors appear to mostly phenocopy pan-BET, especially in oncology, while BD2-selective inhibitors show a more nuanced phenotype appropriate for the treatment of immune-mediated inflammatory diseases …”
Section: Introductionmentioning
confidence: 99%
“…The majority of reported BRD4 inhibitors target BD1 and BD2 indiscriminately. Recently, inhibitors that selectively target BD2 over BD1 revealed an important role of BD2 in the recruitment of BET proteins for gene expression and may provide more effective therapeutic options by avoiding the toxicity associated with inhibition of BD1. Beyond prototypical BRD4 inhibitors, a series of compounds capable of concurrently inhibiting the KAc site of BRD4 and the adenosine triphosphate (ATP) site of certain kinases have been discovered. , Among these dual BRD4-kinase inhibitors are the diaminopyrimidine Janus kinase 2 (JAK2) inhibitors fedratinib and TG101209, the dihydropteridinone PLK1 inhibitors volasertib and BI2536, , and the benzopyrimidodiazipinones LRRK2-IN-1 and ERK5-IN-1. , While these kinase inhibitors have been studied in the context of BRD4 inhibition, their interaction with other BET bromodomains is unknown. Such information, however, may aid the development of BET inhibitors designed to simultaneously target certain BET bromodomains and kinases differentially, depending on the disease application.…”
Section: Introductionmentioning
confidence: 99%
“…The compound RVX-208 was an early BD2-specific compound; however, it exhibited only moderate BD2 potency (>100 nM, IC 50 [the concentration that inhibits response by 50%] = 2 µM in our BRDT-BD2 AlphaScreen assay) and selectivity over BD1 domains (∼10-fold) ( 21 ). More recent efforts from other laboratories and ours have reported the synthesis of pan-BD2 inhibitors with significantly enhanced potency and selectivity [e.g., GSK046 ( 12 ), ABBV-744 ( 22 ), and our CDD-1302 compound ( 23 )].…”
mentioning
confidence: 99%